Psychosocial Determinates of Cognitive Functioning in Older Adults - Arshad, Tehreem; Kausar, Rukhsana; Fatima, Iram (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To examine the predictors of cognitive functioning in older adults of Pakistan. METHODOLOGY: A community-based sample of 243 men and women (age range of 50-75) was drawn through convenient sampling by employing a specific inclusion and exclusion criteria from different cities of Punjab province of Pakistan. We employed the co-relational research design. A set of questionnaires to capture the study variables was administered individually after taking into account the ethical considerations. Data was collected from January 2017 to November 2018. RESULTS: Data was analyzed through Statistical Package for Social Sciences version - 20 (SPSS). It depicted that cognitive functioning is positively associated with education, personality traits of agreeableness, consciousness, and openness, social network of friends and social activity while negative associations were found betweengender, age, neuroticism with cognitive functioning. Regression analysis further showed that age, education, conscientiousness and social activity predict cognitive functioning. CONCLUSION: Age, education, possessing conscientiousness personality trait and more social activities are found as determinates of cognitive functioning in older adults. Implications of these results are further discussed. KEY WORDS: Personality, Social engagement, Social activities, Cognitive functioning.